Association of Statins with Sensory and Autonomic Ganglionopathy - Novak, Peter; Pimentel, Daniela A.; Sundar, Banu; Moonis, Majaz; Qin, Lan; Novak, Vera (Frontiers in Aging Neuroscience, 2015)
Objective: To examine if statins have an effect on small nerve fibers. Methods: This retrospective study evaluated the effect of statins in pure small fiber neuropathy. Outcome measures were symptom scales (numbness, tingling and autonomic symptoms), skin biopsies assessing epidermal nerve fiber density (ENFD), sweat gland nerve fiber density (SGNFD) and quantitative autonomic testing. Results: 160 participants with pure small fiber neuropathy were identified. 80 participants (women/men, age±sd 33/47, 68.1±11.6 years old) were on statins for 53.5±28.7 months for treatment of dyslipidemia and they were age and gender matched with 80 participants (33/47, 68.1±9.5) that were off statins. ANOVA showed reduced ENFD/SGNFD at the proximal leg in the statin group ((count/mm) 8.3±3.6/51.3±14.2) compared to the off statin group (10.4±3.8, p=0.0008/56.4±12.7, p=0.018). There was no difference in ENFD/SGNFD at the distal leg in the statin group (4.9±3.2/39.8±15.7) compared to the off statin group (5.9±3.4, p=0.067/41.8±15.9, p=0.426). Statins did not affect symptom scales and the outcome of autonomic testing. Conclusions: Statin use is associated with degeneration of sensory and autonomic fibers. The pattern of abnormalities, e.g. degeneration of proximal while sparing of distal fibers, is consistent with a non-length dependent process with lesions in the dorsal root and the autonomic ganglia. The statin-associated sensory and autonomic ganglionopathy is mild.